Pertimbangan Hakim terhadap Putusan Verstek pada Perkara Perceraian Nomor 1916/Pdt.G/2022/PA.Tnk - Baharudin, Baharudin; Satria, Indah; Gumilang AS, M. Ariq (Faculty of Law, Institut Ilmu Sosial dan Bisnis Andi Sapada., 2023)
Verdict verstek is a decision handed down by a panel of judges without the presence of the Defendant, and his absence is without a valid reason even though he has been summoned officially and properly. This study uses a normative legal research method with a statutory approach. The purpose of this study is to find out the judge’s consideration of the verstek decision in divorce cases in Decision Number 1916/Pdt.G/2022/PA.Tnk and what reasons made the trial judge in Decision Number 1916/Pdt.G/2022/PA.Tnk decides on divorce cases verstek. The results of the judicial review of the judge’s consideration of the verstek decision in the divorce case in Decision Number 1916/Pdt.G/2022/PA.Tnk is the verstek decision in a contested divorce case. Legal considerations from judges in deciding verstek are contained in Article 149 paragraph 1 Rechtreglement voor de Buitengewesten (RBg). In the absence of the defendant to fulfill the summons without a valid reason, in by Article 125 paragraph 1 and Article 126, the judge can decide verstek. This verstek issue cannot be separated from the provisions of Article 12 Herzien Inlandsch Reglement (HIR), Article 77 Reglement op de Rechtsvordering (Rv) and Article 125 Paragraph 1 HIR, Article 73 Rv and the verstek decision stipulated in Article 125 Paragraphs 1, 2, 3, 4 HIR. The causes of the court judge deciding the verstek divorce case in Decision Number 1916/Pdt.G/2022/PA.Tnk found causal factors, namely that the defendant never attended court even though he had been summoned properly and officially based on the provisions of the applicable laws. As long as the Defendant is not present and is not caused by a reason justified by law—while the Plaintiff’s lawsuit is not against the law—then based on the provisions of Article 149 R.Bg, the Plaintiff’s lawsuit can be granted verstek. ___ Referensi Buku dengan penulis: Fauzan, M. (2005). Pokok-Pokok Hukum Acara Perdata Peradilan Agama dan Mahkamah Syari’ah di Indonesi. Jakarta: Kencana. Manan, Abdul., dan Fauzan, M. (2002). Pokok-pokok Hukum Perdata Wewenang Peradilan Agama. Jakarta: Rajagrafindo Persada. Mukarom, R. (2019). Pertimbangan Hakim terhadap Alasan Perceraian pada Putusan Verstek Cerai Gugat Tahun 2017: Studi 12 Putusan di Pengadilan Agama Sumedang. Bandung: UIN Sunan Gunung Djati Bandung. Rasyid, A. Roihan. (2006). Hukum Acara Peradilan Agama. Jakarta: Rajagrafindo Persada. Soekanto, Soerjono. (1942). Pengantar Penelitian Hukum. Jakarta: Universitas Indonesia. Soemitro, R. H. (1980). Metodologi Penelitian Hukum dan Jurimetri. Jakarta: Ghalia Indonesia. Artikel jurnal: Azizah, L. (2012). Analisis Perceraian dalam Kompilasi Hukum Islam. Al-‘Adalah, 10(2), 415-422. Basir, A. (2023). Analisis Yuridis Perlawanan Pihak Ketiga (Derden Verzet) terhadap Putusan Verstek Sengketa Hak Milik Atas Tanah. Pledoi Law Jurnal, 1(1), 1-9. Darmawati, D., dan Zainuddin, A. (2015). Penerapan Keputusan Verstek di Pengadilan Agama. Al-Mizan (e-Journal), 11(1), 90-101. Mafruh, M. H., Fasa, M. I., dan Ja’far, A. K. (2022). Penyelesaian Sengketa Ekonomi Syariah di Pengadilan Agama pada Masa Pandemi Covid-19. Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 4(2), 542-556. Maswandi, S. H. (2017). Putusan Verstek dalam Hukum Acara Perdata. Jurnal Mercatoria, 10(2), 160-179. Nurdin, M. (2018). Kajian Yuridis Penetapan Sanksi Di Bawah Sanksi Minimum Dalam Penyalahgunaan Narkotika. Jurnal Hukum Samudra Keadilan, 13(2), 270-285. Prasetya, U. (2020). Analisis Asas Audi Et Alteram Partem dalam Proses Persidangan Perkara Perdata (Perkara Nomor 20/Pdt. G/2019/PN Pwr). Amnesti Jurnal Hukum, 2(2), 57-75. Sitorus, S. (2018). Upaya Hukum Dalam Perkara Perdata (Verzet, Banding, Kasasi, Peninjauan Kembali dan Derden Verzet). Hikmah, 15(1), 63-71. Tompo, J., Nurhalifah, N., dan Arsyad, Y. M. (2022). Putusan Verstek terhadap Perkara Perceraian di Pengadilan Agama Sungguminasa Kelas 1 B. Al-Tafaqquh: Journal of Islamic Law, 3(2), 98-107.